Arabidopsis Microtubule-Destabilizing Protein 25 Functions in Pollen Tube Growth by Severing Actin Filaments. Issue 1 (14th January 2014) - Qin, Tao; Liu, Xiaomin; Li, Jiejie; Sun, Jingbo; Song, Leina; Mao, Tonglin
Abstract : This study elucidates a mechanism whereby calcium enhances the actin filament–severing activity of MICROTUBULE-DESTABILIZING PROTEIN25 (MDP25) in the subapical region of pollen tubes, thereby modulating pollen tube growth in Arabidopsis . Abstract: The formation of distinct actin filament arrays in the subapical region of pollen tubes is crucial for pollen tube growth. However, the molecular mechanisms underlying the organization and dynamics of the actin filaments in this region remain to be determined. This study shows that Arabidopsis thaliana MICROTUBULE-DESTABILIZING PROTEIN25 (MDP25) has the actin filament–severing activity of an actin binding protein. This protein negatively regulated pollen tube growth by modulating the organization and dynamics of actin filaments in the subapical region of pollen tubes. MDP25 loss of function resulted in enhanced pollen tube elongation and inefficient fertilization. MDP25 bound directly to actin filaments and severed individual actin filaments, in a manner that was dramatically enhanced by Ca 2+, in vitro. Analysis of a mutant that bears a point mutation at the Ca 2+ binding sites demonstrated that the subcellular localization of MDP25 was determined by cytosolic Ca 2+ level in the subapical region of pollen tubes, where MDP25 was disassociated from the plasma membrane and moved into the cytosol. Time-lapse analysis showed that the F-actin-severing frequency significantly decreased and a high density of actin filaments was observed in the subapical region of mdp25-1 pollen tubes. This study reveals a mechanism whereby calcium enhances the actin filament–severing activity of MDP25 in the subapical region of pollen tubes to modulate pollen tube growth.